2017
DOI: 10.3390/bs7010006
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Economic Hardship and Child Maltreatment Using Data from the Ontario Incidence Study of Reported Child Abuse and Neglect-2013 (OIS-2013)

Abstract: There is strong evidence that poverty and economic disadvantage are associated with child maltreatment; however, research in this area is underdeveloped in Canada. The purpose of this paper is to examine the relationship between economic hardship and maltreatment for families and children identified to the Ontario child protection system for a maltreatment concern. Secondary analyses of the Ontario Incidence Study of Reported Child Abuse and Neglect-2013 (OIS-2013) were conducted. The OIS-2013 examines the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 46 publications
5
41
2
1
Order By: Relevance
“…For instance, the likelihood of CMV infection is higher in children raised in poverty and low socioeconomic status ( 49 , 50 ). Poverty is reliable predictor of more severe forms of ELA such as childhood abuse and neglect ( 51 53 ). There is no clear epidemiological data on the prevalence of infection in international adoptees, as were included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the likelihood of CMV infection is higher in children raised in poverty and low socioeconomic status ( 49 , 50 ). Poverty is reliable predictor of more severe forms of ELA such as childhood abuse and neglect ( 51 53 ). There is no clear epidemiological data on the prevalence of infection in international adoptees, as were included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, levels of education are important predictors of socioeconomic status of the family [67]. Research has shown that lower family socioeconomic situation, resulting in poverty and economic hardships, is an important precursor of child maltreatment [68,69]. On the other hand higher education level with its role in improving socioeconomic status enables people to fulfil their daily needs and respond to demands, relieving stress, and stabilizing the family.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand higher education level with its role in improving socioeconomic status enables people to fulfil their daily needs and respond to demands, relieving stress, and stabilizing the family. In addition education protects parents from involvement in negative bahaviors such as cigarette smoking and alcohol consumption [ 69 71 ]. This could be an explanation of why highly educated fathers are less likely to commit child abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative and dose-response effect of ACEs predicts a greater likelihood of later problems. Likewise, recent and persistent exposures (13)(14)(15), as well as combinations of ACEs (e.g., maternal mental health and poverty) (16) have greater implications for child health. Children with more ACEs have higher rates of infections, asthma and obesity compared to a general paediatric population (17).…”
Section: Life Course Healthmentioning
confidence: 99%